The prosthodontic recovery of the damaged external hexagon due to improper implant position. A case report - Wataru Katagiri; Daisuke Suda; Daichi Hasebe; Akinori Funayama; Tadaharu Kobayashi (Elsevier, 2021)
Improper implant position and the occlusion of the single crown can cause the loosening of the abutment screw. Especially in the external connection system, the abutment screw is easily loosened due to rotation or a lateral force, which will cause damage to the implant body, including the external hexagon.We report a case of a damaged external hexagon that was recovered using prosthetic parts without removing the implant. A 69-year-old female underwent implant placement in the lower left first molar with a long medial cantilever, and a metal bond superstructure was seated. Nine years after implant placement, the external hexagon was found to be damaged. The damaged implant and crown were fixed to the adjacent metal crown using a simple key-and-keyway system.